Edukasi Peningkatan Kesadaran Perlindungan Anak dan Perempuan kepada Masyarakat RW 06 Perak Barat melalui Media Poster: Education to Increase Awareness of the Protection of Children and Women to the Community of RW 06 Perak Barat through Poster Media - Emeraldien, Fikry Zahria; Muthoharoh, Ilal; Madaniah, Aulia; Saputra, Achmad Dhani; Fathoni, Achmad Rafli; Fahmi, R. Mochamad Aqmara (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This research aims to increase public awareness regarding the importance of protecting children and women. Apart from that, to convey information and encourage active participation from the people of RW 06 Perak Barat. This activity was carried out because the security conditions in RW 06 Perak Barat were quite vulnerable. This is due to the location of the RW 06 6 Perak Barat area in the Krembangan sub-district, Surabaya, which is often an alternative route so maximum security is quite difficult to achieve. Educational activities regarding the protection of children and women are carried out through the use of posters. The results of this research are poster media that can encourage active participation in RW 06 Perak Barat related to the urgency of protecting children and women.